Negative active material as well as preparation method and application thereof
By introducing N, O, F impurity elements and oxygen-containing functional groups into carbon-coated silicon anode materials, the carbon layer structure and lithium-ion diffusion are improved, solving the problems of volume expansion and high resistivity of silicon-based anodes, and improving the cycle life and charge/discharge efficiency of lithium batteries.
Patent Information
- Application Number
- CN202410677050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-12-02
AI Technical Summary
Silicon-based anodes in lithium batteries suffer from large volume expansion and high resistivity, leading to reduced cycle life and low charge/discharge efficiency. Existing improvement measures have not been very effective.
Highly electronegative N, O, and F impurity elements are introduced into the carbon layer or surface of carbon-coated silicon anode material, and the first oxygen-containing functional group is introduced into the end face or defect of carbon nanotubes. These are then connected by hydrogen bonds to improve the carbon layer structure and lithium-ion diffusion. Carbon nanotubes are used to suppress the expansion of silicon materials and increase the solid content of the slurry.
It effectively suppresses the expansion of silicon materials during charging and discharging, improves cycle capacity retention and fast charging capability, and enhances electrochemical performance.
Smart Images

Figure CN121054641A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and in particular to a low-expansion silicon anode active material, its preparation method, and its application. Background Technology
[0002] With the increasing depletion of mineral resources, rechargeable lithium-ion batteries, as a clean energy carrier, have gradually gained attention worldwide, ushering in a golden age for lithium-ion batteries. However, many problems still exist in the application of lithium batteries, such as low energy density and poor rate performance. Therefore, battery materials with high capacity and high rate performance have become a key research focus.
[0003] Silicon-based anodes, with a theoretical specific capacity of nearly 4200 mAh / g and a higher lithium intercalation potential than graphite (0.4V vs 0.2V), are considered by the industry to be the ultimate solution for lithium battery development.
[0004] However, silicon-based anodes still face many problems in industrial applications: 1) Large volume expansion during charging and discharging, with an expansion rate exceeding 300%, leading to anode structural failure and significantly reduced cycle life. 2) High material resistivity; the resistivity of silicon powder can reach 10 Ω·m, which is 100-1000 times higher than that of graphite, resulting in large polarization and low coulombic efficiency during charging and discharging.
[0005] To address these issues, the industry has adopted a method of reacting silicon with silicon dioxide to generate silicon suboxide, followed by carbon coating to mitigate volume expansion and reduce resistivity. However, the performance of the materials prepared so far has not been significantly improved and does not meet the requirements of the lithium battery industry. Furthermore, some researchers have added single-walled carbon nanotubes during the anode homogenization process, but simple physical stirring and shearing have failed to achieve satisfactory coating results, leading to poor suppression of volume expansion in the silicon anode.
[0006] Therefore, there is an urgent need for a negative electrode active material that can simultaneously improve the volume expansion and resistivity of silicon-based negative electrodes, so that it can be used in lithium-ion batteries and other applications to improve the battery's cycle life and other electrochemical performance. Summary of the Invention
[0007] In view of this, one objective of this application is to provide a negative electrode active material. By introducing highly electronegative N, O, and F impurity elements into the carbon layer and / or surface of a carbon-coated silicon negative electrode material, the structure of the surface carbon layer can be changed, improving the conductivity of the carbon layer. Furthermore, the impurity elements cause changes in the carbon layer lattice, which facilitates the diffusion of lithium ions into the bulk phase of the material. Simultaneously, a first oxygen-containing functional group is introduced at the end face and / or defects of the carbon nanotubes. The first oxygen-containing functional group is connected to the heteroatoms on the carbon layer through hydrogen bonds with higher bond energy. On the one hand, this allows the carbon nanotubes to be better wound around the modified carbon-coated silicon negative electrode material surface, thereby utilizing the high tensile modulus of the carbon nanotubes to suppress the expansion of the silicon material during charge and discharge, ultimately improving the electrochemical performance of the negative electrode active material, such as the cycle capacity retention rate. On the other hand, this avoids the difficulty of slurry preparation due to the high specific surface area of carbon nanotubes, effectively improving the solid content of the slurry.
[0008] Another objective of this application is to provide a method for preparing a negative electrode active material.
[0009] Another objective of this application is to provide a negative electrode sheet.
[0010] Another object of this application is to provide a secondary battery.
[0011] Another object of this application is to provide an electrical device.
[0012] To achieve the above objectives, the first aspect of this application provides a negative electrode active material, comprising:
[0013] A modified carbon-coated silicon anode material, wherein the modified carbon-coated silicon anode material comprises a carbon-coated silicon anode material and heteroatoms; the carbon-coated silicon anode material comprises a silicon material and a carbon layer at least partially coated on the outer surface of the silicon material, wherein the heteroatoms are disposed inside and / or on the surface of the carbon layer, and the heteroatoms include at least one of the elements O, N, and F;
[0014] Modified carbon nanotubes are wound around the surface of a modified carbon-coated silicon anode material. The modified carbon nanotubes include carbon nanotubes and a first oxygen-containing functional group. The first oxygen-containing functional group is disposed at the end face and / or defects of the carbon nanotubes. The first oxygen-containing functional group is connected to the heteroatom through hydrogen bonds.
[0015] In some embodiments, the first oxygen-containing functional group includes at least one selected from hydroxyl, carboxyl, carbonyl, and ether groups.
[0016] In some embodiments, the heteroatom in the negative electrode active material has an amount of a, where a is 5% to 10%.
[0017] In some embodiments, the first oxygen-containing functional group has an amount of b in the negative electrode active material, where b is 5% to 10%.
[0018] In some implementations, a and b satisfy the following relationship:
[0019] 0.9≤a / b≤1.1.
[0020] In some embodiments, the modified carbon-coated silicon anode material has a mass content of 0.1% to 50% in the anode active material.
[0021] In some embodiments, the modified carbon nanotubes have a mass content of 0.01% to 5% in the negative electrode active material.
[0022] In some embodiments, the silicon material includes SiO2. x , where x is 0.97-1.05.
[0023] In some embodiments, the mass ratio of the silicon material to the carbon layer is (90-99.9):(0.1-10).
[0024] In some embodiments, the SiO x The particle size Dv50 is 5-100nm.
[0025] Preferably, the SiO x The particle size Dv50 is 5-30nm.
[0026] In some embodiments, the particle size Dv50 of the negative electrode active material is 5-50 μm.
[0027] The second aspect of this application discloses a method for preparing a negative electrode active material, comprising:
[0028] The carbon-coated silicon anode material is subjected to a first surface oxidation treatment or heteroatom doping to obtain the modified carbon-coated silicon anode material.
[0029] A second oxygen-containing functional group is introduced into the end face and / or defects of the carbon nanotube by means of a second oxidation treatment, followed by cooling, and reacting with water during the cooling process to convert the second oxygen-containing functional group into the first oxygen-containing functional group, thereby obtaining the modified carbon nanotube.
[0030] The modified carbon-coated silicon anode material and the modified carbon nanotubes are dispersed by sand milling to obtain the anode active material.
[0031] In some embodiments, the oxidant used in the first oxidation treatment and the second oxidation treatment is at least one of perchloric acid, potassium permanganate, and nitric acid.
[0032] In some embodiments, the heteroatom-doped raw materials include at least one of ammonia cyanide, urea, dicyandiamide, polyaniline, polypyrrole, vinylidene fluoride, trifluoroethanol, hydrofluoric acid, perchloric acid, potassium permanganate, and nitric acid.
[0033] In some embodiments, the temperature of the first oxidation treatment is room temperature, and the time of the first oxidation treatment is 0.5-2 hours.
[0034] In some embodiments, the temperature of the second oxidation treatment is 550-900°C, and the time of the second oxidation treatment is 2-4 hours.
[0035] In some embodiments, the amount of oxidant used in the first oxidation treatment is 5 wt% to 20 wt% of the carbon-coated silicon anode material.
[0036] In some embodiments, the amount of oxidant used in the second oxidation treatment is 5 wt% to 20 wt% of the carbon nanotubes.
[0037] In some embodiments, the amount of the heteroatom-doped raw material is 5 wt% to 20 wt% of the carbon-coated silicon anode material.
[0038] In some embodiments, the carbon-coated silicon anode material is surface-doped with heteroatoms, including:
[0039] When the heteroatom-doped raw material is in a liquid state, the heteroatom-doped raw material is mixed with the carbon-coated silicon anode material at room temperature.
[0040] When the heteroatom-doped raw material is solid, the heteroatom-doped raw material is mixed with the carbon-coated silicon anode material at 550-900°C under an inert gas atmosphere.
[0041] In some embodiments, the second oxygen-containing functional group includes at least one selected from ether, carbonyl, hydroxyl, and carboxyl groups.
[0042] In some embodiments, the humidity of the cooling is greater than 40% RH and less than 100% RH, and the water is water vapor from the environment due to the humidity.
[0043] In some embodiments, the cooling temperature is 550-900°C.
[0044] In some embodiments, the cooling time is 2-10 hours.
[0045] In some embodiments, the step of milling and dispersing the modified carbon-coated silicon anode material and the modified carbon nanotubes includes:
[0046] The modified carbon-coated silicon anode material, the modified carbon nanotubes, and the dispersant are dispersed in a solvent by sand milling.
[0047] In some embodiments, the dispersant includes at least one of sodium carboxymethyl cellulose, polyacrylic acid, and polyurethane.
[0048] In some embodiments, the amount of the dispersant is 0.5-2% of the total mass of the modified carbon-coated silicon anode material and the modified carbon nanotubes.
[0049] In some embodiments, the grinding linear velocity used in the grinding dispersion is 5-25 m / s.
[0050] In some embodiments, the solvent includes water.
[0051] In some embodiments, the method for preparing the negative electrode active material further includes the step of preparing a carbon-coated silicon negative electrode material.
[0052] In some embodiments, the method for preparing the carbon-coated silicon anode material includes the following steps:
[0053] (1) Nano-silicon and nano-silica are vaporized and reacted in an inert gas atmosphere and then deposited as silicon material;
[0054] (2) By controlling the particle size of the silicon material obtained in step (1) through crushing, nanoscale silicon material is obtained.
[0055] (3) The nanoscale silicon material obtained in step (2) is coated with gas phase, liquid phase or solid phase carbon to obtain carbon-coated silicon anode material.
[0056] A third aspect of this application provides a negative electrode sheet comprising the negative electrode active material described in this application.
[0057] A fourth aspect of this application discloses a secondary battery comprising the negative electrode sheet described in this application.
[0058] The fifth aspect of this application discloses an electrical device comprising the secondary battery described in this application.
[0059] The negative electrode active material described in this application can bring at least the following beneficial effects:
[0060] 1. By introducing highly electronegative N, O, and F impurities into the carbon layer and / or surface of carbon-coated silicon anode materials, the structure of the surface carbon layer can be altered, improving its conductivity. Furthermore, the impurities cause lattice changes in the carbon layer, facilitating lithium-ion diffusion into the bulk phase of the material. Simultaneously, introducing a first oxygen-containing functional group at the end face and / or defects of the carbon nanotubes, and having this first oxygen-containing functional group connected to heteroatoms on the carbon layer via hydrogen bonds with higher bond energy, allows the carbon nanotubes to better entangle on the modified carbon-coated silicon anode material surface. This, in turn, utilizes the high tensile modulus of the carbon nanotubes to suppress the expansion of the silicon material during charge and discharge, ultimately improving the cycle capacity retention rate of the anode active material. On the other hand, it avoids the difficulties in slurry preparation due to the high specific surface area of carbon nanotubes, effectively increasing the solid content of the slurry.
[0061] 2. By controlling the relationship between the proportion of heteroatoms and the proportion of the first oxygen-containing functional group in the negative electrode active material to meet the relationship defined in this application (0.9≤a / b≤1.1, and a≥5%), the matching between electron conduction rate and ion conduction rate is enhanced, and the negative electrode active material meets the 3C fast charging capability.
[0062] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description
[0063] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings.
[0064] in:
[0065] Figure 1a This is a schematic diagram of the negative electrode active material from one angle, illustrating an exemplary embodiment of this application.
[0066] Figure 1b This is a schematic diagram of the negative electrode active material from another angle, illustrating an exemplary embodiment of this application.
[0067] Figure 2 This is a flowchart illustrating a method for preparing a negative electrode active material, which is an exemplary embodiment of this application.
[0068] Figure 3 A flowchart illustrating a method for preparing a negative electrode active material, as shown in another exemplary embodiment of this application.
[0069] Figure label:
[0070] 1-Modified carbon-coated silicon anode material; 101-Silicon material; 102-Carbon layer; 103-Heteroatoms; 2-Modified carbon nanotubes; 201-Carbon nanotubes; 202-First oxygen-containing functional group; 3-Hydrogen bond. Detailed Implementation
[0071] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0072] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0073] Unless otherwise specified, all raw materials and equipment involved in this application are self-made through commercial means or known methods; and all methods involved are conventional methods unless otherwise specified.
[0074] In this application, room temperature refers to a temperature of 20-30℃.
[0075] The following describes an embodiment of the present application of a negative active electrode material and a method for preparing the negative active electrode material with reference to the accompanying drawings.
[0076] <Negative Electrode Active Materials>
[0077] Figure 1 is a schematic diagram of the negative electrode active material from one angle, as shown in an exemplary embodiment of this application.
[0078] As shown in Figure 1 and Figure 2 As shown, the negative active electrode material in this embodiment includes a modified carbon-coated silicon negative electrode material 1 and a modified carbon nanotube 2. Wherein:
[0079] The modified carbon-coated silicon anode material 1 includes a carbon-coated silicon anode material and heteroatoms 103; the carbon-coated silicon anode material includes a silicon material 101 and a carbon layer 102 at least partially coated on the outer surface of the silicon material, the carbon layer 102 having heteroatoms 103 inside and / or on the surface, the heteroatoms 103 including at least one of O, N, and F elements.
[0080] Modified carbon nanotubes 2 are wound around the surface of modified carbon-coated silicon anode material 1. The modified carbon nanotubes 2 include carbon nanotubes 201 and a first oxygen-containing functional group 202. The first oxygen-containing functional group 202 is disposed at the end face and / or defects of the carbon nanotubes 201. The first oxygen-containing functional group 202 is connected to heteroatoms 103 through hydrogen bonds 3.
[0081] The negative electrode active material described in this application, by introducing highly electronegative N, O, and F impurity elements into the carbon layer and / or surface of the carbon-coated silicon negative electrode material, can change the structure of the surface carbon layer, improve the conductivity of the carbon layer, and the impurity elements cause changes in the carbon layer lattice, which is conducive to the diffusion of lithium ions into the bulk phase of the material. At the same time, a first oxygen-containing functional group is introduced at the end face and / or defects of the carbon nanotubes, and the first oxygen-containing functional group is connected to the heteroatoms on the carbon layer through hydrogen bonds with higher bond energy. On the one hand, the carbon nanotubes can be better wrapped around the surface of the modified carbon-coated silicon negative electrode material, thereby using the high tensile modulus of the carbon nanotubes to suppress the expansion of the silicon material during the charge and discharge process, and ultimately improve the electrochemical performance such as the cycle capacity retention rate of the negative electrode active material. On the other hand, it can avoid the difficulty of slurry preparation due to the high specific surface area of carbon nanotubes, and effectively improve the solid content of the slurry.
[0082] It should be noted that by introducing highly electronegative N, O, and F impurity elements into the carbon layer and / or the surface of the carbon-coated silicon anode material, the structure of the surface carbon layer can be changed and the conductivity of the carbon layer can be improved. The principle is that the crystal structure of the carbon layer is theoretically sp2 hybridized between C elements. After introducing other atoms, the electron clouds between the atoms change, thereby improving the electron adsorption capacity.
[0083] In some embodiments, the first oxygen-containing functional group 202 includes, but is not limited to, at least one of hydroxyl, carboxyl, carbonyl, ether, etc.
[0084] In some embodiments, the amount of heteroatoms in the negative electrode active material is 'a', where 'a' is 5% to 10%, including but not limited to 5%, 6%, 7%, 8%, 9%, or 10%. When the amount of heteroatoms in the negative electrode active material is within the above range, it can better alter the surface carbon layer structure and improve conductivity; below 5%, the improvement in conductivity decreases slightly; above 10%, the material type changes significantly, and the resistivity increases significantly.
[0085] As an alternative example, when the heteroatoms are O and N, the ratio of the amount of substance of heteroatom O to the amount of substance of heteroatom N is (0.1-5):(0.1-5), including but not limited to 0.1:4.9, 0.5:4.5, 1:4, 2:3 or 4:1, etc.
[0086] As another alternative example, when the heteroatoms are O and F, the ratio of the amount of substance of heteroatom O to the amount of substance of heteroatom F is (0.1-5):(0.1-5), including but not limited to 0.1:4.9, 0.5:4.5, 1:4, 2:3 or 4:1, etc.
[0087] As another alternative example, when the heteroatoms are N and F, the ratio of the amount of substance of heteroatom N to the amount of substance of heteroatom F is (0.1-5):(0.1-5), including but not limited to 0.1:4.9, 0.5:4.5, 1:4, 2:3 or 4:1, etc.
[0088] As another alternative example, when the heteroatoms are O, N, and F, the ratio n of the amount of substance of heteroatom O, the amount of substance of heteroatom N, and the amount of substance of heteroatom F is... o :n N :n F = (0.1-5):(0.1-5):(0.1-5), including but not limited to 0.1:0.1:4.8, 1:1:3, 2:1:2 or 3:0.5:1.5, etc.
[0089] In some embodiments, the first oxygen-containing functional group has a molar percentage of b in the negative electrode active material, where b is 5% to 10%. This includes, but is not limited to, 5%, 6%, 7%, 8%, 9%, or 10%. When the molar percentage of the first oxygen-containing functional group in the negative electrode active material is within the above range, it allows for better bonding with heteroatoms on the carbon layer via hydrogen bonds, achieving a better winding effect on the carbon-coated silicon negative electrode material, thereby better suppressing the volume expansion of the silicon material during charging and discharging. If the percentage is below 5%, the hydrogen bonding decreases, the winding effect deteriorates, and the effect of suppressing the volume expansion of the silicon material during charging and discharging weakens. If the percentage is above 10%, the conductivity advantage brought by the high graphitization of the carbon nanotubes is destroyed, and the conductivity advantage is lost.
[0090] In some implementations, a and b satisfy the following relationship:
[0091] 0.9≤a / b≤1.1.
[0092] In the embodiments of this application, the molar ratio 'a' of heteroatoms in the negative electrode active material and the molar ratio 'b' of the first oxygen-containing functional group in the negative electrode active material satisfy the above relationship, thereby enhancing the matching between electronic conduction rate and ion conduction rate. Because the heteroatoms on the carbon layer of the modified carbon-coated silicon negative electrode material are hydrogen-bonded to the first oxygen-containing functional group on the conductive carbon nanotube, the electronic resistance between the materials is significantly reduced, thus enabling the negative electrode active material to meet the 3C fast charging capability.
[0093] As a non-restrictive example, the values of a / b include, but are not limited to, 0.9, 0.95, 1, 1.05, or 1.1.
[0094] In some embodiments, the modified carbon-coated silicon anode material has a mass content of 0.1% to 50% in the anode active material, including but not limited to 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, or 50%.
[0095] In some embodiments, the modified carbon nanotubes have a mass content of 0.01% to 5% in the negative electrode active material, including but not limited to 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0096] In some embodiments, the silicon material includes SiO2. x , where x is 0.97-1.05.
[0097] As a non-restrictive list, the values of x include, but are not limited to, 0.97, 0.98, 0.99, 1, 1.01, 1.02, 1.03, 1.04, or 1.05.
[0098] In some embodiments, the mass ratio of silicon material to carbon layer is (90-99.9):(0.1-10), including but not limited to 90:10, 95:5, 98:2, 99:1 or 99.5:0.5.
[0099] In some embodiments, the raw materials for forming the carbon layer include, but are not limited to, at least one of methane, acetylene, resin, glucose, asphalt, etc.
[0100] In the embodiments of this application, the carbon layer may be coated on part or all of the surface of the silicon material in a continuous or discontinuous manner.
[0101] In some implementations, the carbon layer continuously coats the entire outer surface of the silicon material.
[0102] It should be noted that in the embodiments of this application, when the carbon layer is discontinuous or only covers part of the outer surface of the silicon material, the expansion suppression effect will be worse.
[0103] In some implementations, SiO x The particle size Dv50 is 5-100nm, including but not limited to 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm.
[0104] As a preferred example, SiO x The particle size Dv50 is 5-30nm.
[0105] In the embodiments of this application, SiO x The particle size Dv50 refers to the particle size of SiO2. x In the volume-based particle size distribution, starting from the smallest particle size, the particle size (diameter) corresponding to 50% of the cumulative volume is measured.
[0106] In some embodiments, carbon nanotubes include, but are not limited to, at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, etc.
[0107] In some embodiments, the particle size Dv50 of the negative electrode active material in this application is 5-50 μm, including but not limited to 10 μm, 20 μm, 30 μm, 40 μm or 50 μm.
[0108] In the embodiments of this application, the particle size Dv50 of the negative electrode active material refers to the particle size (particle size) that corresponds to 50% of the cumulative volume in the volume-based particle size distribution of the negative electrode active material, starting from the smallest particle size.
[0109] The negative electrode active material of this application embodiment can be prepared by the preparation method of the negative electrode active material of this application embodiment.
[0110] <Preparation Methods of Negative Electrode Active Materials>
[0111] In the preparation method of the negative electrode active material in the embodiments of this application, the carbon-coated silicon negative electrode material can be a commercially available carbon-coated silicon negative electrode material or a self-made carbon-coated silicon negative electrode material.
[0112] Figure 2 This is a flowchart illustrating a method for preparing a negative electrode active material, as shown in an exemplary embodiment of this application. Figure 2 As shown, the carbon-coated silicon anode material used in this preparation method is a commercially available carbon-coated silicon anode material. The specific preparation method includes the following steps:
[0113] S101. The carbon-coated silicon anode material is subjected to a first surface oxidation treatment or heteroatom doping to obtain a modified carbon-coated silicon anode material.
[0114] In some embodiments, the oxidant used in the first oxidation treatment includes, but is not limited to, at least one of perchloric acid, potassium permanganate, nitric acid, etc.
[0115] In some embodiments, the temperature of the first oxidation treatment is room temperature.
[0116] In some embodiments, the duration of the first oxidation treatment is 0.5-2 hours, including but not limited to 0.5 hours, 0.8 hours, 1 hour, 1.5 hours, or 2 hours.
[0117] In some embodiments, the first oxidation treatment is carried out under stirring conditions.
[0118] As an alternative example, the method of the first oxidation treatment includes: stirring and oxidizing the carbon-coated silicon anode material with the oxidant of the first oxidation treatment.
[0119] In some embodiments, the amount of oxidant used in the first oxidation treatment is 5-20 wt% of the carbon-coated silicon anode material, including but not limited to 5 wt%, 8 wt%, 10 wt%, 15 wt%, or 20 wt%.
[0120] In some embodiments, the heteroatom-doped raw materials include, but are not limited to, at least one of ammonia cyanide, urea, dicyandiamide, polyaniline, polypyrrole, vinylidene fluoride (VDF), trifluoroethanol (TFE), hydrofluoric acid, perchloric acid, potassium permanganate, and nitric acid.
[0121] It is understandable that ammonia cyanide, urea, dicyandiamide, polyaniline, and polypyrrole are raw materials doped with heteroatoms nitrogen (N); vinylidene fluoride (VDF), trifluoroethanol (TFE), and hydrofluoric acid are raw materials doped with heteroatoms fluorine (F); and perchloric acid, potassium permanganate, and nitric acid are raw materials doped with heteroatoms oxygen (O).
[0122] In some embodiments, the amount of heteroatom-doped raw material is 5-20 wt% of the carbon-coated silicon anode material, including but not limited to 5 wt%, 8 wt%, 10 wt%, 15 wt%, or 20 wt%.
[0123] As an alternative example, when the heteroatoms are O and N, the mass ratio of the O-doped raw material to the N-doped raw material is (0.22-11.1):(0.22-11.1), including but not limited to 0.22:10.89, 1.11:10, 2.22:8.89, 4.44:6.67, or 8.89:2.22, etc.
[0124] As another alternative example, when the heteroatoms are O and F, the mass ratio of the O-doped raw material to the F-doped raw material is (0.22-11.1):(0.22-11.1), including but not limited to 0.22:10.89, 1.11:10, 2.22:8.89, 4.44:6.67 or 8.89:2.22, etc.
[0125] As another alternative example, when the heteroatoms are N and F, the mass ratio of the heteroatom N-doped raw material to the heteroatom N-doped raw material is (0.22-11.1):(0.22-11.1), including but not limited to 0.22:10.89, 1.11:10, 2.22:8.89, 4.44:6.67 or 8.89:2.22, etc.
[0126] As another alternative example, when the heteroatoms are O, N, and F, the mass ratio of the O-doped raw material, the N-doped raw material, and the F-doped raw material is m. o :m:m F = (0.22-11.1):(0.22-11.1):(0.22-11.1), including but not limited to 0.22:0.22:10.67, 2.22:2.22:6.67, 4.44:2.22:4.44 or 6.67:1.11:3.33, etc.
[0127] In some embodiments, the carbon-coated silicon anode material is surface-doped with heteroatoms, including:
[0128] When the heteroatom-doped raw material is in liquid state, the heteroatom-doped raw material is mixed with the carbon-coated silicon anode material at room temperature.
[0129] When the heteroatom-doped raw material is solid, the heteroatom-doped raw material is mixed with carbon-coated silicon anode material at 550-900℃ under an inert gas atmosphere.
[0130] In some embodiments, when the heteroatom-doped raw material is solid, the inert gas includes, but is not limited to, at least one of nitrogen, helium, argon, etc.
[0131] In some embodiments, the mixing method during the surface heteroatom doping process of carbon-coated silicon anode material includes, but is not limited to, at least one of stirring, ball milling, and ultrasonic dispersion.
[0132] In some embodiments, when the heteroatom-doped raw material is solid, the mixing temperature includes, but is not limited to, 550°C, 600°C, 700°C, 800°C, or 900°C.
[0133] S102. A second oxygen-containing functional group is introduced into the end face and / or defects of the carbon nanotube by means of a second oxidation treatment, followed by cooling, and reacting with water during the cooling process to transform the second oxygen-containing functional group into a first oxygen-containing functional group, thereby obtaining a modified carbon nanotube.
[0134] In some embodiments, the oxidant used in the second oxidation treatment includes, but is not limited to, at least one of perchloric acid, potassium permanganate, nitric acid, etc.
[0135] In some embodiments, the temperature of the second oxidation treatment is 550-900°C, including but not limited to 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, or 900°C.
[0136] As a preferred example, the temperature of the second oxidation treatment is 600-720°C.
[0137] In some embodiments, the second oxidation treatment time is 0.5-4 hours, including but not limited to 0.5 hours, 1 hour, 2 hours, 3 hours or 4 hours.
[0138] In some embodiments, the second oxidation treatment is carried out under stirring conditions.
[0139] As an alternative example, the second oxidation treatment method includes: stirring carbon nanotubes with an oxidant for the second oxidation treatment to induce oxidation.
[0140] In some embodiments, the amount of oxidant used in the second oxidation treatment is 5-20 wt% of the carbon nanotubes, including but not limited to 5 wt%, 8 wt%, 10 wt%, 15 wt%, or 20 wt%.
[0141] In some embodiments, the second oxygen-containing functional group includes, but is not limited to, at least one of ether, carbonyl, hydroxyl, and carboxyl groups.
[0142] In some implementations, the cooling humidity is greater than 40% RH and less than 100% RH, for example, 41% RH, 50% RH, 60% RH, 70% RH, 80% RH or 90% RH, etc.
[0143] In some embodiments, the above-mentioned reaction with water occurs during the cooling process, wherein the water is water vapor in the environment caused by the humidity (greater than 40% RH and less than 100% RH).
[0144] It should be noted that in the embodiments of this application, when the cooling humidity is below 40% RH, the above-mentioned reaction with water during the cooling process can also be water vapor added to the reaction system. In this case, the amount of water added is 5-50 wt% of carbon nanotubes, including but not limited to 5 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, or 50 wt%.
[0145] In some embodiments, the cooling temperature is 550-900°C, including but not limited to 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, or 900°C.
[0146] In some implementations, the cooling time is 2-10 hours, including but not limited to 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours.
[0147] It should be noted that, in the embodiments of this application, since the water reacts during the cooling process, that is, the cooling and the reaction with water occur simultaneously, the temperature at which the water reacts is also the cooling temperature, and the time at which the water reacts is also the cooling time.
[0148] S103. The modified carbon-coated silicon anode material and the modified carbon nanotubes are dispersed by sand milling to obtain the anode active material.
[0149] In the embodiments of this application, the purpose of sand milling and dispersing the modified carbon-coated silicon anode material and the modified carbon nanotubes is to enable the carbon layer of the modified carbon-coated silicon anode material to form hydrogen bond connections with the first oxygen-containing functional group.
[0150] In some embodiments, the modified carbon-coated silicon anode material and the modified carbon nanotubes are dispersed by sand milling, including:
[0151] Modified carbon-coated silicon anode material, modified carbon nanotubes, and dispersant were dispersed in a solvent by sand milling.
[0152] In some embodiments, the dispersant includes, but is not limited to, at least one of sodium carboxymethyl cellulose, polyacrylic acid (PAA), etc.
[0153] It should be noted that in the embodiments of this application, when two or more of sodium carboxymethyl cellulose and polyacrylic acid (PAA) are used as dispersants, the multiple dispersants can be mixed in any mass ratio.
[0154] In some embodiments, the amount of dispersant used is 0.5-2% of the total mass of the modified carbon-coated silicon anode material and the modified carbon nanotubes, including but not limited to 0.5%, 0.8%, 1%, 1.5% or 2%.
[0155] In some embodiments, the grinding linear velocity used in the grinding dispersion is 5-25 m / s, including but not limited to 5 m / s, 10 m / s, 15 m / s, 20 m / s or 25 m / s.
[0156] In some embodiments, the solvent includes, but is not limited to, water, wherein water includes deionized water.
[0157] In some embodiments, the total mass of the modified carbon-coated silicon anode material, the modified carbon nanotubes, and the dispersant in the solvent is 5-50%, including but not limited to 5%, 10%, 20%, 30%, 40%, or 50%.
[0158] In some embodiments, the preparation method of the above-mentioned negative electrode active material further includes a step of spray drying the product after sand milling and dispersion.
[0159] It should be noted that in the embodiments of this application, the order of steps S101 and S102 can be interchanged.
[0160] Figure 3 A flowchart illustrating a method for preparing a negative electrode active material, as shown in another exemplary embodiment of this application. Figure 3 As shown, the carbon-coated silicon anode material in this preparation method is a self-made carbon-coated silicon anode material, and the specific preparation method includes the following steps:
[0161] S201. Prepare carbon-coated silicon anode material.
[0162] In some embodiments, the preparation of carbon-coated silicon anode materials includes:
[0163] (1) Nano-silicon and nano-silica are vaporized and reacted in an inert gas atmosphere and then deposited as silicon material;
[0164] (2) By controlling the particle size of the silicon material obtained in step (1) through crushing, nanoscale silicon material is obtained.
[0165] (3) The nanoscale silicon material obtained in step (2) is coated with gas phase, liquid phase or solid phase carbon to obtain carbon-coated silicon anode material.
[0166] In some embodiments, in step (1), the mass ratio of nano-silicon to nano-silica is (0.98-1.07):(1.01-1.02), including but not limited to 0.98:1.01, 0.99:1.01, 1.02:1.02, 1.05:1.01 or 1.07:1.02, etc.
[0167] In some embodiments, in step (1), the inert gas includes, but is not limited to, at least one of nitrogen, helium, argon, etc.
[0168] In some embodiments, the process conditions for the gasification reaction in step (1) are: high-temperature heating to above 800°C. For example, high-temperature heating to 810°C, 850°C, 900°C, or 950°C, etc.
[0169] In some implementations, in step (1), the deposition is a cooling deposition.
[0170] In some embodiments, the temperature for cooling deposition is 600-800°C, including but not limited to 600°C, 650°C, 700°C, or 750°C.
[0171] In some embodiments, in step (2), the pulverization method includes, but is not limited to, at least one of air jet milling, ball milling, etc.
[0172] In some embodiments, the gas phase coating method in step (3) is as follows: a certain amount of carbon source gas to be deposited is introduced into the material reaction vessel, and the material is kept in a stirring and reciprocating state.
[0173] In some embodiments, in step (3), the carbon source coated in the gas phase includes, but is not limited to, at least one of acetylene, methane, ethylene, ethane, etc.
[0174] In some embodiments, in step (3), the liquid phase coating method is as follows: the reactants (i.e., the above-mentioned nanoscale silicon material) and the deposited carbon source are mixed and stirred evenly in a reaction vessel and then heated to complete the liquid phase coating.
[0175] In some embodiments, in step (3), the carbon source coated in the liquid phase includes, but is not limited to, at least one of sugars, resins, liquid organic matter, etc.
[0176] By way of a non-limiting example, sugars include, but are not limited to, at least one of glucose, sucrose, etc.
[0177] By way of non-limiting example, resins include, but are not limited to, at least one of phenolic resins, furan resins, epoxy resins, etc.
[0178] By way of a non-limiting example, liquid organic matter includes, but is not limited to, at least one of petroleum residue, petroleum slurry, and mineral oil.
[0179] In some embodiments, in step (3), the solid phase coating method is as follows: the reactants (i.e., the above-mentioned nanoscale silicon material) and the carbon source of the deposit are mixed and stirred evenly in a reaction vessel and then heated to liquefy the deposit.
[0180] In some embodiments, in step (3), the carbon source of the solid phase coating includes, but is not limited to, at least one of solid organic materials such as coal tar pitch and petroleum pitch.
[0181] It should be noted that, in the embodiments of this application, the method for preparing carbon-coated silicon anode material, in addition to the method containing steps (1)-(3) above, can also be any well-known method in the art for preparing carbon-coated silicon anode material.
[0182] S202. The carbon-coated silicon anode material is subjected to a first surface oxidation treatment or heteroatom doping to obtain a modified carbon-coated silicon anode material.
[0183] In the embodiments of this application, the specific implementation of step S202 is the same as that of the aforementioned step S101, and will not be repeated here.
[0184] S203. A second oxygen-containing functional group is introduced into the end face and / or defects of the carbon nanotube by means of a second oxidation treatment, followed by cooling, and reacting with water during the cooling process to transform the second oxygen-containing functional group into a first oxygen-containing functional group, thereby obtaining a modified carbon nanotube.
[0185] In the embodiments of this application, the specific implementation of step S203 is the same as that of step S102 described above, and will not be repeated here.
[0186] S204. The modified carbon-coated silicon anode material and the modified carbon nanotubes are dispersed by sand milling to obtain the anode active material.
[0187] In the embodiments of this application, the specific implementation of step S203 is the same as that of step S103 described above, and will not be repeated here.
[0188] In some embodiments, the preparation method of the above-mentioned negative electrode active material further includes a step of spray drying the product after sand milling and dispersion.
[0189] It should be noted that in the embodiments of this application, steps S201 and S202 need to be performed sequentially, but their overall operation order can be interchanged with step S203.
[0190] The method for preparing the negative electrode active material in this application embodiment can bring at least the following beneficial effects:
[0191] 1) By introducing highly electronegative impurity elements N, O, and F into the carbon layer on the surface of silicon material in carbon-coated silicon anode materials and / or onto the surface, the structure of the surface carbon layer is changed, which can improve the conductivity of the carbon layer. Furthermore, the impurity elements cause changes in the carbon layer lattice, which is conducive to the diffusion of lithium ions into the bulk phase of the material.
[0192] 2) By oxidizing carbon nanotubes, oxygen-containing functional groups are introduced and hydrogen bonds are generated between them and heteroatoms on the carbon layer. This allows the carbon nanotubes to better wrap around the modified carbon-coated silicon anode material, thereby achieving the goal of suppressing the volume expansion of silicon material during charging and discharging.
[0193] 3) By controlling the ratio of impurity atoms on the surface of carbon-coated silicon anode material to oxygen-containing functional groups in carbon nanotubes, the matching between electron conduction rate and ion conduction rate is enhanced, and the material meets the 3C fast charging capability.
[0194] 4) The high specific surface area of carbon nanotubes is connected by hydrogen bonds between heteroatoms and the first oxygen-containing functional group on the carbon layer, which avoids the difficulty of pulping and effectively improves the solid content of the pulp.
[0195] <Negative electrode sheet>
[0196] The negative electrode sheet of this application embodiment includes the negative electrode active material of this application embodiment.
[0197] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. The negative electrode film layer includes a negative electrode active material, which includes the negative electrode active material of the embodiments of this application.
[0198] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0199] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0200] In some embodiments, the negative electrode active material, in addition to the negative electrode active material of the embodiments of this application, may also contain negative electrode active materials known in the art for use in batteries. As examples, these known negative electrode active materials for batteries may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the embodiments of this application are not limited to these materials and may also include other conventional materials that can be used as negative electrode active materials for batteries. These negative electrode active materials may be used alone or in combination of two or more.
[0201] In some embodiments, the negative electrode film layer may optionally include a negative electrode binder. The negative electrode binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0202] In some embodiments, the negative electrode film layer may optionally include a negative electrode conductive agent. The negative electrode conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0203] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0204] In some embodiments, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, negative electrode conductive agent, negative electrode binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0205] Secondary batteries
[0206] The secondary battery of this application embodiment includes the negative electrode sheet of this application embodiment.
[0207] In some embodiments, the secondary battery includes lithium-ion batteries, etc.
[0208] [Positive electrode plate]
[0209] In some embodiments, the aforementioned secondary battery also includes a positive electrode.
[0210] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector.
[0211] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0212] The positive electrode film includes the positive electrode active material. The positive electrode active material can be selected from materials that can absorb and release lithium.
[0213] The specific type of the positive electrode active material is not specifically limited and can be selected according to requirements. As an example, the positive electrode active material may include, but is not limited to, lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel-type lithium manganese oxide (LiMn2O4), spinel-type lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium manganate (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, for example LiNi 0.8 Co 0.15 Al 0.05 O2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, for example LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, etc.), lithium-rich materials (such as lithium-rich nickel cobalt manganese oxide), manganese dioxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and at least one of their respective modified compounds. These materials can be used alone or in combination of two or more.
[0214] The modified compounds of the above positive electrode active materials can be doping modification, surface coating modification, or simultaneous doping and coating modification of the positive electrode active material.
[0215] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0216] In some embodiments, the positive electrode film layer may optionally include a positive electrode binder. As an example, the positive electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0217] In some embodiments, the positive electrode film may optionally include a positive electrode conductive agent. As an example, the positive electrode conductive agent may include, but is not limited to, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0218] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, positive conductive agent, positive binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0219] [Isolation membrane]
[0220] In some embodiments, the secondary battery also includes a separator.
[0221] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0222] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0223] [Electrolytes]
[0224] In some embodiments, the secondary battery of this application also includes an electrolyte.
[0225] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid.
[0226] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes electrolyte salts and non-aqueous organic solvents.
[0227] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0228] In some embodiments, the non-aqueous organic solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0229] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0230] In some embodiments, when the electrolyte is a solid electrolyte, the solid electrolyte includes, but is not limited to:
[0231] LISICON type: such as γ-Li3PO4, etc.;
[0232] NASICON type; for example, Li (1+x1) Q x M (2-x1) (PO4)3, 0≤x1<1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, and La;
[0233] Garnet type; for example, Li (7-x2) La3Zr (2-x2) M x2 O12, etc., 0≤x2<1, M includes at least one of Sb, Nb, Ta, Te, and W;
[0234] LIPON type: for example, Lix3 PO y1 N z1 ; 0 < x3 ≤ 1, 0 < y1 ≤ 1, 0 < z1 ≤ 1; <00Type: where -2 < x6 < 2, 0 ≤ y3 ≤ 2, 0 ≤ z3 ≤ 2, and M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo; A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, and H includes at least one of F, Cl, Br, I: (100 - x7)Li2S·x7M·y4Q type: where 20 ≤ x7 ≤ 30, 0 ≤ y4 ≤ 50, and M includes at least one of B2S3, Al2S3, In2S3, SiS2, GeS2, SnS2, P2S5, As2S3, Sb2S5, Bi2S3, WS2, MoS2; Q includes at least one of B2O3, Al2O3, In2O3, SiO2, GeO2, SnO2, P2O5, Sb2O5, Bi2O3, WO2, WO3, MoO2, MoO3, Fe2O3, ZnO, MgO, CuO, CaO, LiN, Li2O, LiF, LiCl, LiBr, LiI; Argyrodite type: Li (6+x8) M y5 A (1-y5) Q (5-z5) T (1+z5) , where -1 ≤ x8 ≤ 1, 0 ≤ y5 ≤ 1, -1 < z5 ≤ 1, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, Mo, A includes at least one of P, As, Sb, Bi, Q includes at least one of S, Se, and T includes at least one of F, Cl, Br, I; Halide type: Li3MJ or Li2Sc 2 / 3 J; M includes at least one of Y, Er, In, Sc, Ga, and J includes at least one of F, Cl, Br, I.
[0238] When the above sulfide solid electrolyte is a sulfide-based solid electrolyte, it includes but is not limited to: argyrodite electrolyte; binary sulfide-based solid systems such as Li2S-P2S5, Li2S-SiS2, Li2S-GeS, and Li2S-B2S3, and Li2S-Me-P2S5 ternary systems, where Me is selected from Si, Ge, Sn, or Al, etc.
[0239] Specifically, the above sulfide electrolyte is selected from at least one of Li2S-P2S5, Li2S-SiS2, Li2S-GeS, Li2S-B2S3, and Li2S-Me-P2S5.
[0240] In some embodiments, the positive electrode sheet, negative electrode sheet, and separator can be made into an electrode assembly by a winding process or a stacking process.
[0241] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode assembly and electrolyte.
[0242] In some embodiments, the outer packaging of a secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of a secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0243] This application does not impose any particular restrictions on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape.
[0244] <Electrical Appliances>
[0245] The electrical device in this application includes the secondary battery in this application.
[0246] In some embodiments, the aforementioned electrical devices include, but are not limited to, vehicles, lighting devices, electronic devices, etc.
[0247] The negative electrode sheet, secondary battery, and power-consuming device of the present application embodiments all have at least the beneficial effects of the negative electrode active material and the preparation method of the negative electrode active material of the present application embodiments.
[0248] The following non-limiting embodiments further illustrate certain features of the present technology.
[0249] I. Examples and Comparative Examples
[0250] Example 1
[0251] (Negative electrode active material)
[0252] As shown in Figure 1, the negative electrode active material of this embodiment includes a modified carbon-coated silicon negative electrode material 1 and modified carbon nanotubes 2. Wherein:
[0253] The modified carbon-coated silicon anode material 1 comprises a carbon-coated silicon anode material and heteroatoms 103; the carbon-coated silicon anode material comprises a silicon material 101 and a carbon layer 102 coated on the outer surface of the silicon material, with a mass ratio of silicon material to carbon layer of 95:5. The silicon material 101 is SiO2. x Where x is 1.01; SiO x The particle size Dv50 is 30 nm. The carbon layer 102 continuously coats the entire outer surface of the silicon material; heteroatoms 103, which are oxygen elements, are provided inside and on the surface of the carbon layer 102.
[0254] Modified carbon nanotubes 2 are wound around the surface of a modified carbon-coated silicon anode material 1. The modified carbon nanotubes 2 include carbon nanotubes 201 and a first oxygen-containing functional group 202. The carbon nanotubes are single-walled carbon nanotubes. The first oxygen-containing functional group 202 is located at the end face and defects of the carbon nanotube 201, and is connected to the carbon layer 102 by hydrogen bonds 3. The first oxygen-containing functional group 202 is composed of hydroxyl and carboxyl groups.
[0255] The molar percentage of heteroatoms in the negative electrode active material is a, and the molar percentage of the first oxygen-containing functional group in the negative electrode active material is b, a / b = 0.94; a is 8%, and b is 8.5%.
[0256] The modified carbon-coated silicon anode material has a mass content of 98% in the anode active material; the modified carbon nanotubes have a mass content of 2% in the anode active material.
[0257] The particle size Dv50 of the negative electrode active material in this embodiment is 25 μm.
[0258] (Preparation method of negative electrode active material)
[0259] The preparation method of the negative electrode active material in this embodiment includes the following steps:
[0260] (1) Preparation of modified carbon-coated silicon anode material
[0261] ①Silicon and silicon dioxide are pulverized to a particle size of 5-30 nm by air jet milling to obtain nano-silicon and nano-silicon dioxide;
[0262] ②The nano-silicon and nano-silica obtained in step ① are vaporized in a nitrogen atmosphere at 1300℃ for 3 hours at a mass ratio of 1:1.01, and then cooled to room temperature to deposit solid silicon material.
[0263] ③ The silicon material obtained in step ② is pulverized to a particle size Dv50 of 30 nm by air jet milling;
[0264] ④ The silicon material pulverized in step ③ is mixed with phenolic resin at a mass ratio of 92:8 and then carbonized at 1250℃ under a nitrogen atmosphere for 2 hours to obtain carbon-coated silicon anode material.
[0265] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with perchloric acid with a purity >70wt% at a mass ratio of 92:8 and stirred at 10r / min for 60min at room temperature to perform the first oxidation treatment, thereby obtaining the modified carbon-coated silicon anode material.
[0266] (2) Preparation of modified carbon nanotubes
[0267] Single-walled carbon nanotube powder was mixed with perchloric acid with a purity >70wt% at a mass ratio of 91.5:8.5 and stirred at 10r / min for 60min at room temperature for a second oxidation treatment, introducing ether groups and carbonyl groups at the end faces and defects of the single-walled carbon nanotubes. Subsequently, the mixture was cooled for 6h in an environment with 80% humidity and 25℃, allowing the ether groups and carbonyl groups to react with water during the cooling process to form hydroxyl and carboxyl groups, thus obtaining modified carbon nanotubes.
[0268] (3) Composite of modified carbon nanotubes and modified carbon-coated silicon anode material
[0269] Using sodium carboxymethyl cellulose as a dispersant, the modified carbon-coated silicon anode material, modified carbon nanotubes, and dispersant were dispersed in deionized water at a mass ratio of 98:0.5:1.5 (the total mass of the modified carbon-coated silicon anode material, modified carbon nanotubes, and dispersant was 20% of the mass of deionized water) by sand milling at a linear velocity of 12 m / s for 3 hours. Then, the mixture was spray-dried at 250°C to obtain the anode active material of this embodiment.
[0270] Example 2
[0271] This embodiment is basically the same as embodiment 1, except that:
[0272] In the negative electrode active material, silicon material is SiO x Where x is 1.01; SiO x The particle size Dv50 is 10 nm; the heteroatom 103 is F element. The molar percentage of heteroatoms in the negative electrode active material is a, and the molar percentage of the first oxygen-containing functional group in the negative electrode active material is b, a / b = 1.1; a is 5.5%, and b is 5%.
[0273] In the preparation method of the negative electrode active material, step (1) of the preparation method of the modified carbon-coated silicon negative electrode material includes the following steps:
[0274] ①Silicon and silicon dioxide are pulverized to a particle size of 5-30 nm by air jet milling to obtain nano-silicon and nano-silicon dioxide;
[0275] ②The nano-silicon and nano-silica obtained in step ① are vaporized at a mass ratio of 1:1.01 in a nitrogen atmosphere at 1300℃ for 3 hours, and then cooled to room temperature to deposit solid silicon material.
[0276] ③ The silicon material obtained in step ② is pulverized to a particle size Dv50 of 10 nm by air jet milling;
[0277] ④ The silicon material pulverized in step ③ is mixed with petroleum asphalt at a mass ratio of 92:8 and then carbonized at 1250℃ under a nitrogen atmosphere for 1.5 hours to obtain carbon-coated silicon anode material.
[0278] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with hydrofluoric acid with a purity >50wt% at a mass ratio of 95.5:4.5 and stirred at 10r / min for 40min at room temperature to perform heteroatom doping, thereby obtaining modified carbon-coated silicon anode material.
[0279] In step (2), single-walled carbon nanotube powder and perchloric acid with a purity >70wt% are mixed at a mass ratio of 95:5 and stirred at 12r / min for 180min at 25℃ for a second oxidation treatment.
[0280] Example 3
[0281] This embodiment is basically the same as embodiment 1, except that:
[0282] In the negative electrode active material, silicon material is SiO x Where x is 1; SiO x The particle size Dv50 is 16 nm; the heteroatom 103 is nitrogen. The molar percentage of heteroatoms in the negative electrode active material is 'a', and the molar percentage of the first oxygen-containing functional group in the negative electrode active material is 'b', a / b = 0.94; a is 6.6%, and b is 7.0%.
[0283] In the preparation method of the negative electrode active material, step (1) of the preparation method of the modified carbon-coated silicon negative electrode material includes the following steps:
[0284] ①Silicon and silicon dioxide are pulverized to a particle size of 5-30 nm by air jet milling to obtain nano-silicon and nano-silicon dioxide;
[0285] ② The nano-silicon and nano-silica obtained in step ① were vaporized in a nitrogen atmosphere at 1300℃ for 3 hours at a mass ratio of 1:1, and then cooled to room temperature to deposit solid silicon material.
[0286] ③ The silicon material obtained in step ② is pulverized to a particle size Dv50 of 16 nm by air jet milling;
[0287] ④ The silicon material pulverized in step ③ is mixed with acetylene at a mass ratio of 92:8 and then carbonized at 1250℃ under a nitrogen atmosphere for 2 hours to obtain carbon-coated silicon anode material.
[0288] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with polypyrrole at a mass ratio of 93.4:6.6 and stirred at 10 r / min for 200 min at 600 °C under a nitrogen protective atmosphere to perform heteroatom doping, thereby obtaining the modified carbon-coated silicon anode material.
[0289] In step (2), single-walled carbon nanotube powder and potassium permanganate are mixed at a mass ratio of 93:7 and stirred at 10 r / min for 60 min at 100℃ for a second oxidation treatment.
[0290] Example 4
[0291] This embodiment is basically the same as embodiment 1, except that:
[0292] In the negative electrode active material, silicon material is SiO x Where x is 1.03; SiO x The particle size Dv50 is 40 nm; the heteroatom 103 is an oxygen element. The molar percentage of heteroatoms in the negative electrode active material is 'a', and the molar percentage of the first oxygen-containing functional group in the negative electrode active material is 'b', a / b = 1.03; a is 6%, and b is 5.8%.
[0293] In the preparation method of the negative electrode active material, step (1) of the preparation method of the modified carbon-coated silicon negative electrode material includes the following steps:
[0294] ①Silicon and silicon dioxide are pulverized to a particle size of 5-30 nm by air jet milling to obtain nano-silicon and nano-silicon dioxide;
[0295] ②The nano-silicon and nano-silica obtained in step ① are vaporized in a nitrogen atmosphere at 1300℃ for 3 hours at a mass ratio of 1:1.03, and then cooled to room temperature to deposit solid silicon material.
[0296] ③ The silicon material obtained in step ② is pulverized to a particle size Dv50 of 40 nm by air jet milling;
[0297] ④ The silicon material pulverized in step ③ is mixed with acetylene at a mass ratio of 92:8 and then carbonized at 1250℃ under a nitrogen atmosphere for 2 hours to obtain carbon-coated silicon anode material.
[0298] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with potassium permanganate at a mass ratio of 94:6 and stirred at 10 r / min for 50 min at 100 °C under a nitrogen protective atmosphere to perform heteroatom doping, thereby obtaining the modified carbon-coated silicon anode material.
[0299] In step (2), single-walled carbon nanotube powder and perchloric acid with a purity >70wt% are mixed at a mass ratio of 94.2:5.8 and stirred at 10r / min for 55min at 25℃ for a second oxidation treatment.
[0300] Example 5
[0301] This embodiment is basically the same as embodiment 1, except that:
[0302] In the negative electrode active material, silicon material is SiO x Where x is 0.97; SiO x The particle size Dv50 is 50 nm; the heteroatom 103 is nitrogen. The molar percentage of heteroatoms in the negative electrode active material is 'a', and the molar percentage of the first oxygen-containing functional group in the negative electrode active material is 'b', a / b = 0.90; a is 5.2%, and b is 5.8%.
[0303] In the preparation method of the negative electrode active material, step (1) of the preparation method of the modified carbon-coated silicon negative electrode material includes the following steps:
[0304] ①Silicon and silicon dioxide are pulverized to a particle size of 5-30 nm by air jet milling to obtain nano-silicon and nano-silicon dioxide;
[0305] ②The nano-silicon and nano-silica obtained in step ① are vaporized at a mass ratio of 1:0.95 in a nitrogen atmosphere at 1300℃ for 3 hours, and then cooled to room temperature to deposit solid silicon suboxide.
[0306] ③ The silicon suboxide obtained in step ② is pulverized by air jet milling to a particle size Dv50 of 50 nm;
[0307] ④ The pulverized silicon suboxide from step ③ is mixed with phenolic resin at a mass ratio of 92:8 and then carbonized at 1250℃ under a nitrogen atmosphere for 2 hours to obtain carbon-coated silicon anode material.
[0308] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with polypyrrole at a mass ratio of 94.8:5.2 and stirred at 9 r / min for 60 min at 100 °C to perform heteroatom doping, thereby obtaining the modified carbon-coated silicon anode material.
[0309] In step (2), single-walled carbon nanotube powder and potassium permanganate are mixed at a mass ratio of 94.2:5.8 and stirred at 10 r / min for 50 min at 100℃ for a second oxidation treatment.
[0310] Example 6 (Heteroatoms are O and F)
[0311] This embodiment is basically the same as embodiment 1, except that:
[0312] In the negative electrode active material, heteroatoms 103 are O and F elements, and their mass ratio is 1:1.
[0313] In the preparation method of negative electrode active material, in step (1) the preparation method of modified carbon-coated silicon negative electrode material:
[0314] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with heteroatom doping raw material at a mass ratio of 92:8 and stirred at 10 r / min for 60 min at room temperature to perform heteroatom doping, thereby obtaining modified carbon-coated silicon anode material; wherein the heteroatom doping raw material is a mixture of perchloric acid with a purity >70 wt% and hydrofluoric acid with a purity >50 wt% in a mass ratio of 1:1.
[0315] Example 7 (Heteroatoms are O, N, and F)
[0316] This embodiment is basically the same as embodiment 1, except that:
[0317] In the negative electrode active material, the heteroatoms 103 are O, N, and F elements, and the mass ratio of the three is 1:1:1. In the preparation method of the negative electrode active material, in step (1) the preparation method of the modified carbon-coated silicon negative electrode material:
[0318] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with heteroatom doping raw materials at a mass ratio of 92:8 and stirred at 10 r / min for 60 min at 100 °C under a nitrogen protective atmosphere to perform heteroatom doping, thereby obtaining modified carbon-coated silicon anode material; wherein the heteroatom doping raw materials are a mixture of perchloric acid with a purity >70 wt%, polypyrrole, and hydrofluoric acid with a purity >50 wt% in a mass ratio of 1:1:1.
[0319] Example 8 (F-doped raw materials are a mixture)
[0320] This embodiment is basically the same as embodiment 2, except that:
[0321] In the preparation method of negative electrode active material, in step (1) the preparation method of modified carbon-coated silicon negative electrode material:
[0322] Step 5 is as follows: The carbon-coated silicon anode material obtained in step 4 is mixed with heteroatom doping raw material at a mass ratio of 95.5:4.5 and stirred at 10 r / min for 60 min at room temperature to dope the material, thereby obtaining the modified carbon-coated silicon anode material; wherein, the heteroatom doping raw material is a mixture of hydrofluoric acid with a purity >50 wt% and trifluoroethanol mixed at a mass ratio of 1:1.
[0323] Example 9 (Substitute for N-doped raw materials)
[0324] This embodiment is basically the same as embodiment 3, except that:
[0325] In the preparation method of negative electrode active material, in step (1) the preparation method of modified carbon-coated silicon negative electrode material:
[0326] ⑤ The carbon-coated silicon anode material obtained in step ④ is mixed with urea at a mass ratio of 93.4:6.6 and stirred at 8 r / min for 50 min at 600 °C under a nitrogen protective atmosphere to perform heteroatom doping, thereby obtaining the modified carbon-coated silicon anode material.
[0327] Example 10 (The carbon nanotubes are multi-walled carbon nanotubes)
[0328] This embodiment is basically the same as embodiment 1, except that:
[0329] In both the negative electrode active material and the preparation method of the negative electrode active material, the carbon nanotubes are multi-walled carbon nanotubes.
[0330] Example 11 (The carbon-coated silicon anode material is a commercially available product)
[0331] This embodiment is basically the same as embodiment 1, except that:
[0332] The carbon-coated silicon anode material is model BSO-1, produced by BTR New Materials Group.
[0333] Example 12 (Different Humidity Levels)
[0334] This embodiment is basically the same as embodiment 1, except that:
[0335] The modified carbon nanotubes were mixed with the modifier and then cooled in an environment with 41% humidity.
[0336] Comparative Example 1
[0337] This comparative example is basically the same as Example 1, except that:
[0338] The carbon-coated silicon anode material obtained in Example 1 was directly mixed with single-walled carbon nanotubes at a mass ratio of 98:0.5 to obtain the anode active material.
[0339] Comparative Example 2
[0340] This comparative example is basically the same as Example 1, except that:
[0341] In the preparation method of the negative electrode active material, step (2) is not included. In step (3), the single-walled carbon nanotubes are directly combined with the modified carbon-coated silicon negative electrode material.
[0342] Comparative Example 3
[0343] This comparative example is basically the same as Example 1, except that:
[0344] In the preparation method of the negative electrode active material, the carbon-coated silicon negative electrode material is not modified. That is, the preparation process of the modified carbon-coated silicon negative electrode material in step (1) does not include step ⑤. In step (3), the modified carbon nanotubes are directly combined with the carbon-coated silicon negative electrode material.
[0345] II. Material Characterization and Performance Testing
[0346] 1. Material Characterization
[0347] Material powder resistivity: The negative electrode active materials of each embodiment and comparative example were tested according to the static resistivity test method in national standard GB / T40007.
[0348] 2. Slurry solids content test
[0349] The negative electrode active material, negative electrode conductive agent carbon black SP, negative electrode dispersant sodium carboxymethyl cellulose and negative electrode binder styrene-butadiene rubber (SBR, item number P886285, Maclean) of the examples or comparative examples are dispersed in water at a mass ratio of 96:1:1:2 and stirred to form a uniform negative electrode slurry.
[0350] After controlling the output viscosity of the negative electrode slurry of each embodiment or comparative example to 3000-4000 mPa·s, the slurry was dried at 120°C and the solid content was tested.
[0351] 3. Electrochemical performance testing
[0352] 3.1 Battery Assembly
[0353] The negative electrode active materials of each embodiment and comparative example were used as negative electrode sheets, and then assembled into C2032 coin cells for electrochemical performance testing.
[0354] The assembly method for the C2032 button cell includes the following steps:
[0355] 1) Preparation of negative electrode sheet: The negative electrode active material, negative electrode conductive agent carbon black SP, negative electrode dispersant sodium carboxymethyl cellulose and negative electrode binder styrene-butadiene rubber (SBR, item number P886285, Maclean) were dispersed in water at a mass ratio of 96:1:1:2, with a solid content of 50wt%, and stirred to form a uniform negative electrode slurry; then the negative electrode slurry was coated onto the surface of a clean copper foil using a coater, and then placed in a vacuum oven to be vacuum dried at 120℃ for 12h, and rolled to obtain a compaction of 1.5mg / mm 3 The negative electrode sheet.
[0356] 2) Battery Assembly: Using the negative electrode obtained in step 1), a lithium sheet as the counter electrode, and a Celgard 2400 polypropylene membrane as the separator, the batteries were assembled into 2032 button cells in an argon-filled glove box with the electrolyte. The electrolyte used in assembling the 2032 button cells was a 1 mol / L LiPF6 solution obtained by dissolving LiPF6 in a mixed solvent of ethyl carbonate (EC) and diethyl carbonate (DMC) (volume ratio EC:DMC = 1:1).
[0357] 3.2 Electrochemical performance testing
[0358] (1) Cyclic capacity retention
[0359] The reversible capacity and capacity retention of the coin cells (i.e., secondary batteries) involved in the embodiments or comparative examples were tested using a Newway tester (model: CT 4008Tn 5V20mA 164). Specifically, this included: constant current and constant voltage charging at 0.1C, and charge-discharge cycle testing at a discharge rate of 0.1C. The capacity retention rate after 50 cycles was calculated as: discharge capacity after 50 cycles at 0.1C / discharge capacity of the first cycle at 0.1C * 100%. The voltage range for the charge-discharge test was between 0.005 and 2V.
[0360] (2) Ratio performance
[0361] The capacity retention of the coin cells (i.e., secondary cells) involved in each embodiment or comparative example was tested under 3C charging and 1C discharging at room temperature (25°C). The voltage range for the charge and discharge tests was between 0.005 and 2V.
[0362] The results of the solid content test and electrochemical performance test of the slurry are shown in Table 1.
[0363] Table 1. Results of Solid Content and Electrochemical Performance Tests of the Slurry
[0364]
[0365] As can be seen from the data in Table 1, the resistivity of the hydrogen-bonded silicon & carbon nanotube composite powder was significantly reduced after modification, and the cycle capacity retention was significantly improved.
[0366] Meanwhile, controlling the particle size of silicon materials to be smaller and optimizing the uniformity of carbon coating both significantly improve the high-temperature cycling capacity retention of the materials. Comparing Example 1 and Example 4, the oxidation treatment with potassium permanganate during heteroatom doping is slightly less effective than that with perchloric acid. Comparing Example 1 and Example 5, N doping has a more significant effect on improving the volume resistivity of the powder, consistent with the principle that CN has better electronegativity than C-OH.
[0367] Furthermore, by comparing Example 1 and Comparative Examples 1-3, it can be found that: Example 1 combines the modified carbon-coated silicon anode material with the modified carbon nanotubes. Compared with the case where neither the carbon-coated silicon anode material nor the carbon nanotubes are modified in this application or only one of them is modified, higher anode slurry solid content, lower resistivity, and better rate performance and cycle capacity retention can be obtained.
[0368] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0369] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly indicating the number, specific order, or primary and secondary relationship of the indicated technical features.
[0370] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0371] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0372] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces), unless otherwise explicitly specified.
[0373] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0374] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
Claims
1. A negative electrode active material, characterized in that, include: A modified carbon-coated silicon anode material, wherein the modified carbon-coated silicon anode material comprises a carbon-coated silicon anode material and heteroatoms; the carbon-coated silicon anode material comprises a silicon material and a carbon layer at least partially coated on the outer surface of the silicon material, wherein the heteroatoms are disposed inside and / or on the surface of the carbon layer, and the heteroatoms include at least one of the elements O, N, and F; Modified carbon nanotubes are wound around the surface of a modified carbon-coated silicon anode material. The modified carbon nanotubes include carbon nanotubes and a first oxygen-containing functional group. The first oxygen-containing functional group is disposed at the end face and / or defects of the carbon nanotubes. The first oxygen-containing functional group is connected to the heteroatom through hydrogen bonds.
2. The negative electrode active material according to claim 1, characterized in that, The first oxygen-containing functional group includes at least one of hydroxyl, carboxyl, carbonyl, and ether groups.
3. The negative electrode active material according to claim 1, characterized in that, The heteroatom in the negative electrode active material has a mass percentage of a, where a is 5% to 10%. And / or, the first oxygen-containing functional group has an amount of b in the negative electrode active material, wherein b is 5% to 10%.
4. The negative electrode active material according to claim 3, characterized in that, a and b satisfy the following relationship: 0.9≤a / b≤1.
1.
5. The negative electrode active material according to claim 1, characterized in that, The modified carbon-coated silicon anode material has a mass content of 90% to 99.9% in the anode active material; And / or, the modified carbon nanotubes in the negative electrode active material have a mass content of 0.1% to 10%.
6. The negative electrode active material according to claim 1, characterized in that, The silicon material includes SiO₂. x , where x is 0.97-1.05; And / or, the mass ratio of the silicon material to the carbon layer is (90-99.9):(0.1-10).
7. The negative electrode active material according to claim 6, characterized in that, The SiO x The particle size Dv50 is 5-100 nm; Optionally, the SiO x The particle size Dv50 is 5-30nm.
8. The negative electrode active material according to claim 1, characterized in that, The particle size Dv50 of the negative electrode active material is 5-50 μm.
9. A method for preparing a negative electrode active material as described in any one of claims 1 to 8, characterized in that, include: The carbon-coated silicon anode material is subjected to a first surface oxidation treatment or heteroatom doping to obtain the modified carbon-coated silicon anode material. A second oxygen-containing functional group is introduced into the end face and / or defects of the carbon nanotube by means of a second oxidation treatment, followed by cooling, and reacting with water during the cooling process to convert the second oxygen-containing functional group into the first oxygen-containing functional group, thereby obtaining the modified carbon nanotube. The modified carbon-coated silicon anode material and the modified carbon nanotubes are dispersed by sand milling to obtain the anode active material.
10. The preparation method according to claim 9, characterized in that, The oxidants used in the first oxidation treatment and the second oxidation treatment are at least one of perchloric acid, potassium permanganate, and nitric acid; And / or, the heteroatom-doped raw materials include at least one of ammonia cyanide, urea, dicyandiamide, polyaniline, polypyrrole, vinylidene fluoride, trifluoroethanol, hydrofluoric acid, perchloric acid, potassium permanganate, and nitric acid.
11. The preparation method according to claim 9, characterized in that, The temperature of the first oxidation treatment is room temperature, and the time of the first oxidation treatment is 0.5-2 hours; And / or, the temperature of the second oxidation treatment is 550-900℃, and the time of the second oxidation treatment is 2-4h; And / or, the amount of oxidant used in the first oxidation treatment is 5 wt% to 20 wt% of the carbon-coated silicon anode material; And / or, the amount of oxidant used in the second oxidation treatment is 5 wt% to 20 wt% of the carbon nanotubes; And / or, the amount of the heteroatom-doped raw material is 5 wt% to 20 wt% of the carbon-coated silicon anode material.
12. The preparation method according to claim 9, characterized in that, The carbon-coated silicon anode material is surface-doped with heteroatoms, including: When the heteroatom-doped raw material is in a liquid state, the heteroatom-doped raw material is mixed with the carbon-coated silicon anode material at room temperature. When the heteroatom-doped raw material is solid, the heteroatom-doped raw material is mixed with the carbon-coated silicon anode material at 550-900°C under an inert gas atmosphere.
13. The preparation method according to claim 9, characterized in that, The second oxygen-containing functional group includes at least one of ether, carbonyl, hydroxyl, and carboxyl groups; And / or, the humidity of the cooling is greater than 40% RH and less than 100% RH, and the water is water vapor from the environment caused by the humidity; And / or, the cooling temperature is 550-900°C; And / or, the cooling time is 2-10 hours.
14. The preparation method according to claim 9, characterized in that, The step of milling and dispersing the modified carbon-coated silicon anode material and the modified carbon nanotubes includes: The modified carbon-coated silicon anode material, the modified carbon nanotubes, and the dispersant were dispersed in a solvent by sand milling. And / or, the method for preparing the negative electrode active material further includes the step of preparing a carbon-coated silicon negative electrode material.
15. The preparation method according to claim 14, characterized in that, The dispersant includes at least one of sodium carboxymethyl cellulose and polyacrylic acid; And / or, the amount of the dispersant is 0.5-2% of the total mass of the modified carbon-coated silicon anode material and the modified carbon nanotubes; And / or, the grinding linear velocity used in the grinding dispersion is 5-25 m / s; And / or, the solvent includes water; And / or, the method for preparing the carbon-coated silicon anode material includes the following steps: (1) Nano-silicon and nano-silica are vaporized and reacted in an inert gas atmosphere and then deposited as silicon material; (2) By controlling the particle size of the silicon material obtained in step (1) through crushing, nanoscale silicon material is obtained. (3) The nanoscale silicon material obtained in step (2) is coated with gas phase, liquid phase or solid phase carbon to obtain carbon-coated silicon anode material.
16. A negative electrode sheet, characterized in that, Includes the negative electrode active material as described in any one of claims 1 to 8.
17. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 16.
18. An electrical appliance, characterized in that, Includes the secondary battery as described in claim 17.
Citation Information
Cited By
Preparation method of self-cleaning polytetrafluoroethylene composite membrane
CN121466838A